Cigarette Design Features in Low-, Middle-, and High-Income Countries. (8th May 2012) - Caruso, Rosalie V.; O'Connor, Richard J.
Abstract : Previous studies have shown that country income grouping is correlated with cigarette engineering. Cigarettes (N = 111 brands) were purchased during 2008–2010 from 11 low-, middle-, and high-income countries to assess physical dimensions and an array of cigarette design features. Mean ventilation varied significantly across low- (7.5%), middle- (15.3%), and high-income (26.2%) countries (P ≤ 0.001 ). Differences across income groups were also seen in cigarette length (P = 0.001 ), length of the tipping paper (P = 0.01 ), filter weight (P = 0.017 ), number of vent rows (P = 0.003 ), per-cigarette tobacco weight (P = 0.04 ), and paper porosity (P = 0.008 ). Stepwise linear regression showed ventilation and tobacco length as major predictors of ISO tar yields in low-income countries (P = 0.909, 0.047), while tipping paper (P < 0.001 ), filter length (P < 0.001 ), number of vent rows (P = 0.014 ), and per-cigarette weight (P = 0.015 ) were predictors of tar yields in middle-income countries. Ventilation (P < 0.001 ), number of vent rows (P = 0.009 ), per-cigarette weight (P < 0.001 ), and filter diameter (P = 0.004 ) predicted tar yields in high-income countries. Health officials must be cognizant of cigarette design issues to provide effective regulation of tobacco products.